From 'passive custodian' to 'active advocate': tracing the emergence and sport-internal transformative effects of sport policy advocacy. Issue 3 (3rd July 2019) - Stenling, Cecilia; Sam, Mike
ABSTRACT: Organised sport has become a legitimate interest group, with potential influence in wider policy-making circles. Building on a distinction between because-of motives and in-order-to motives, the purpose of this study is to analyse why sport organisations conduct advocacy while offering an assessment of the sport-internal transformative effects of advocacy activities. The analysis is based on interviews with 46 elected and staff representatives of Swedish Regional Sport Federations, and it shows (1) that a perceived de-institutionalization of organised sport's monopolistic position in Sweden underpins the imperative to conduct advocacy, and (2) that the overarching goal-oriented purpose of advocacy is to further sport organisations' role as advocates in future policy processes. This indicates that sport organisations are transitioning from a 'passive custodian' to an 'active advocate' role in relation to the government. We propose that this latter role may include a professionalisation of advocacy activities, and that advocacy, therefore, may accentuate internal tensions related to the trade-off between efficiency and democracy, create a need for sport-internal advocacy, and undermine future advocacy claims and/or access to policy processes.